PERUBAHAN TUTUPAN HUTAN DAERAH PERTAMBANGAN KOTA SAWAHLUNTO TAHUN 2009 SAMPAI 2019 - Elsi Agusri Dewi; Ratna Wilis (JURUSAN GEOGRAFI FIS UNP, 2019)
Abstract This research was conducted in the mining area of ​​Sawahlunto City which aims to look at forest cover changes of mining areas in 2009 to 2014 and 2014 to 2019 and also to see deforestation occurring and to see the rate of deforestation. The method used in this research is descriptive quantitative approach and the data used are secondary data. Land cover was obtained from Landsat 5 TM and Landsat 8 OLI imagery using supervised classification methods. The results of the identification of forest cover changes in 2009 to 2014 showed a reduction in the area from 3,572 hectares to 3,556 hectares reduced by 16 hectares and in 2014 to 2019 showed a very significant change from 3,556 hectares to 3,150 hectares reduced by 406 hectares with an area of ​​deforestation for 10 years covering an area of ​​607 hectares with a deforestation rate of 0.66% or an area of ​​34.95 hectares per year. Accuracy test of images carried out using confusion matrix (comparison of image interpretation with field conditions) with an accuracy of 88,43%.